Everything you need to know about dyslexia - Goldish, Meish (New York : Rosen Pub. Group, 1998)
Explains the causes and symptoms of dyslexia and discusses how to overcome this disability and become a good reader and writer.
Includes bibliographical references (p. 62) and index.
Accelerated Reader AR
Keywords: Dyslexia -- Juvenile literature; Dyslexic children -- Education -- Juvenile literature; Dyslexic children -- Services for -- Juvenile literature